O sistema de normas ISO e as nanotecnologias: as interfaces regulatórias e o diálogo entre as fontes do direito - Martins, Patricia Santos (Universidade do Vale do Rio dos Sinos, 2016)
In view of the current state of the art of nanotechnologies, promises and risks, the present study aims to assess the extent to which ISO standards can be used as a tool to address metaregulation in order to overcome the current lack of nanospecific regulatory frameworks. To this end, it intends to clarify the context of nanotechnologies, their characteristics risks and applications. There are several applications and advantages brought about by nanotechnology development, but investments in safety research are still proportionally lower than the resources destined to the development and commercialization of products with applied nanotechnologies and their results are not conclusive. In view of these statements and human interference in the creation of (engineered) nanoparticles, it is important to verify their insertion within the risk zone drawn by Niklas Luhmann's risk theory, and to analyze the regulatory models of self-regulation and metregulation. Regulatory models already used by organizations through the adoption of tools recognized as ISO technical standards, which base actions to demonstrate the conduct and transparency with respect to good business practices in the development of activities. Part of the proposed analysis is the dialogue between the sources of law and the actors of normative production in the light of the theory of legal pluralism, to envisage the possibility of these technical standards acting as a regulatory interface and analyzing in this interface the legal effectiveness. Finally, it will seek to know ISO its norms and its processes of creation and revision of technical norms, and also to study its structuring elements in face of the principles of Law and fundamental rights, to verify the possibility of recognizing the technical norms of ISO management as legitimate Minimum regulatory threshold. The methodology used is functionalist, historical and comparative, through research techniques indirect documentation, especially bibliographic research, besides direct documentation to normative and legal texts as well as texts resulting from the scientific production of several areas of knowledge, using Features such as content analysis.
Keywords: Normas técnicas ISO; Nanotecnologias; Autorregulação; Teoria do risco; Pluralismo jurídico; Empresário cidadão; ISO Technical standards; Nanotechnologies; Self-regulation; Sources; Risk theory; Legal pluralism; Businessman; ACCNPQ::Ciências Sociais Aplicadas::Direito